Workshop Digital Talent Perakitan dan Optimasi PC untuk Pemberdayaan Masyarakat Pati di Era Digital - Anin Maftukhah; Muhammad Atiq; Danang Hendrawan; Raka Dian Mahardi; Muhammad Reyhan F (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2026)
The rapid development of the digital era requires human resources to not only master software, but also understand hardware infrastructure. This community service program aims to improve the technical competence and digital literacy of the people of Pati Regency through a PC assembly and optimization workshop. The method used is the Participatory Action Learning Sistem (PALS), in collaboration with "Pati Tech" as an industry partner, and utilizing the campus computer laboratory as a training center. Activities consisted of orientation, planning, and hands-on practice in PC assembly. The results of the community service program showed a significant increase in the technical skills of participants, as reflected in the average pre-test score of 52.5 which increased to 86.4 in the post-test. Participants are now able to assemble and optimize sistem independently. The implication of this activity is the formation of independent digital talents who can manage digital infrastructure, which is expected to support the development of the local creative economy in Pati Regency. This program contributes to improving technological skills relevant to the needs of the digital market.